Value-based utility implementation in software-defined testbed for sensor data traffic management - Alipio, Melchizedek Ibarrientos (Animo Repository, 2019)
Data transmitted among wireless sensor nodes are generated from sensing physical events with diverse traffic types. These data have to reach their destinations with a specific Quality of Service (QoS) requirement. With the increasing usage of sensors in various Internet of Things applications, there is a need to address the traffic management for handling these critical data while satisfying their respective QoS requirements. In this work, we implemented a traffic management mechanism using Value-based Utility (VBU) model that utilizes network packet statistics to cope with QoS requirement of each sensor data. The mechanism ensures that the demands of each sensor data are satisfied by allocating queue resources based on a utility function. The function defines an expectation range and the state where minimal requirements are met for each sensor. We evaluated the performance of the mechanism over a simple low-cost software-defined testbed with different sensor data type having different QoS requirements. Results show that each sensor node achieved the level of satisfaction based on their required utility function both in an ideal testbed scenario and in an actual indoor deployment. © 2019 Elsevier B.V.